Appearance Design Method of Ceramic Art Based on VR Visualization Technology - Hui Li (Journal of Robotics)
In order to improve the effect of ceramic art appearance design, this work studies the appearance design method of ceramic art combined with VR visualization technology and builds an intelligent model. According to the needs of the industrial site and the requirements of the lighting system, the area type of the lighting area is determined in this study, and the light of the virtual ceramic product is irradiated on the target detection plane through the refraction of the lens. Based on the Lambertian luminescence characteristics of the point light source virtual ceramic products and the uniform distribution of illuminance on the lighting surface, a mathematical model of the lighting system is established. Taking the realization of a rectangular lighting area with high uniformity as the main goal, the mathematical model is used to construct a system of partial differential equations of free-form surfaces, and the effect of the method in this study is verified by combining with the simulation research. The experimental research shows that the appearance design system of ceramic art based on VR visualization technology proposed in this study has a good effect and can effectively improve the interaction effect of appearance design of ceramic art.